Is NordicTrack Exercise a Comparable Substitute for Cross-Country Skiing? - Shih, C.; Tarnowski, E.; Yang, C.
The objective of this study was to analyze the motions during NordicTrack and cross-country skiing to determine whether NordicTrack is a comparable exercise to cross-country skiing. Hip joint range of motion was much greater in cross-country skiing. Also, ankle joint velocity in the horizontal direction was greater in cross-country skiing because the body translated forward. The trunk range of motion and angular velocity slightly were greater during NordicTrack skiing. However, knee joint range of motion was similar in the NordicTrack and cross-country skiing cycles. The NordicTrack machine has a hip pad which allowed for greater body support but restricted hip flexion. In cross-country skiing, hip range of motion was nearly two times that of NordicTrack. This kinematic result has implications that NordicTrack may not work the leg muscles to the same degree as cross-country skiing. Having had much more experience in cross-country skiing, the subject was able to move at a faster pace than on the NordicTrack. This was the main reason for the difference in ankle joint velocity in the horizontal direction. In comparison with a study done on Olympic cross-country skiers who attained an average maximum speed of 14.9 meters per second (Street, G.M. & Gregory, R.W., 1994), the subject in this study only attained a maximum velocity of -4.5 meters per second. Due to the short distance the subject skied, the instructions given to ski at a comfortable pace, and having not trained specifically for this event, limitations were placed on the maximum speed the subject achieved. The differences found with the trunk segment in regards to range of motion and angular velocity were deemed negligible after the movies were examined. It appeared that in both the cross-country and NordicTrack cycles, the trunk segment went through similar motions. Any differences between the two cycles was due to twisting of the upper body and protraction and retraction of the shoulder girdle. Knee joint range of motion was similar in the NordicTrack and cross-country skiing as was expected because there were no specific restrictions placed on this joint in either movement. One limitation involved with this study was the placement of joint markers which may not have been accurate for every single frame analyzed; this may have led to distorted data. Also, this study only examined the movements of one subject who had more experience in cross-country skiing than NordicTrack; the use of multiple subjects with equal experience in both exercises would make this study more valid. Further studies comparing these two movements may analyze the affects of inclines and declines on the biomechanics of skiing.